Production of HMF-derivatives from wine residues using Saccharomyces cerevisiae as whole-cell biocatalyst - Joana T. Cunha; Aloia Romaní; Lucília Domingues (Bioresources and Bioprocessing)
Abstract Background There is an urgent need to develop bioprocesses independent of fossil resources to address resource depletion and mitigate environmental harm. Transitioning to a bio-based economy requires prioritizing chemical production processes that utilize renewable resources, ensuring sustainability and environmental responsibility. 5-Hydroxymethylfurfural (HMF) and its derivatives are promising building blocks, ranked among the top 12 bio-based molecules derived from biomass. This study investigates the potential of wine residues as substrates for HMF production and explores the yeast Saccharomyces cerevisiae, a robust industrial microbial cell factory, as a whole-cell biocatalyst for converting HMF into high-value compounds, offering an alternative to chemical synthesis. Findings Several S. cerevisiae strains were compared for their ability to convert HMF, demonstrating varying capacities for oxidation or reduction. For the first time, HMF derivatives with potential industrial applications were produced using an HMF-rich hydrolysate obtained from sustainable processing of wine-growing waste, such as grape pomace and must surplus. The selected yeast strain was engineered to express the oxidoreductase enzyme of HMF/Furfural from Cupriavidua basilensis strain HMF14, resulting in a 15-fold increase in the accumulation of oxidized derivatives such as 2,5-furandicarboxylic acid (FDCA). Conclusions These findings highlight the potential of leveraging wine residues and engineered S. cerevisiae strains to develop sustainable bioprocesses for producing valuable HMF derivatives, thereby contributing to the advancement of bio-based chemical production. Graphical Abstract